Feasibility of Sharia Oversight on Regulations Outside the Jurisdiction of the Administrative Justice Court - Ali Fattahi Zafarghandi; Hamid Feli; Mohsen Abolhasani (دانش حقوق عمومی)
According to the fourth article of the Constitution of the Islamic Republic of Iran, all acts and regulations must be based on Islamic norms, and it is the responsibility of the jurists of the Guardian Council to recognize them. On the other hand, the proceedings of lawsuits concerning government regulations, according to Articles 170 and 173 of the Constitution, fall under the jurisdiction of the General Board of the Court of Administrative Justice. It is based on this that the possibility of filing a lawsuit against government regulations for the violation of the Sharia rights of individuals, through inquiries from the jurists of the Guardian Council, is foreseen in Articles 84 and 87 of the Code of Organizations and Procedures of the Court of Administrative Justice. According to the jurists of the Guardian Council, compliance is mandatory for this court. Due to the departure of some regulations and approvals from the jurisdiction of the General Board of the Court of Administrative Justice, the main question of this research is: which category of regulations and approvals outside the jurisdiction of the Court of Administrative Justice can be reviewed by the jurists of the Guardian Council upon receiving a complaint in the Court of Administrative Justice? The findings of the research, using a descriptive and analytical method by referring to library sources, show that due to reasons such as the duty of the court to follow the opinions of the jurists of the Guardian Council, the criterion for identifying the jurisdiction of Sharia supervision over regulations, and the fourth article of the Constitution, Sharia supervision over regulations outside the jurisdiction of the Court of Administrative Justice is possible through complaints received in this court.